1994
DOI: 10.1021/bi00201a017
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescence and Optically Detected Magnetic Resonance Investigation of the Binding of the Nucleocapsid Protein of the Human Immunodeficiency Virus Type 1 and Related Peptides to RNA

Abstract: The RNA and DNA complexes of nucleocapsid protein p7.Zn (NCp7.Zn) of the human immunodeficiency virus type 1 (HIV-1) are studied by phosphorescence and optically detected magnetic resonance (ODMR). The single tryptophan, Trp37, which is located on the C-terminal zinc finger domain is used as an intrinsic probe. Reductions in the triplet state zero-field splitting (zfs) D parameter of Trp37 upon complex formation with poly(I) and poly(U) are observed. These results, in conjunction with the phosphorescence red-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
(30 reference statements)
5
33
0
4
Order By: Relevance
“…The isolated different domains of the (12-53)NCp7 are unable to anneal tRNA 3 Lys to RNA-(77-257). Fixed concentrations of [ 33 P]tRNA 3 Lys and RNA-(77-257) (5.10 Ϫ12 mol of each denaturated RNA/ assay) were incubated in a buffer with 25 mM Tris-HCl (pH 7.5), 0.1 mM MgCl 2 , and 80 mM NaCl, for 30 min at 37°C, in the presence of 20, 80, and 150 molar equivalents of (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) NCp7 (lanes 2-4, respectively), (34 -51)NCp7 (lanes 5-7, respectively), and (13-56)NCp7dd (lanes 8 -10, respectively). Lane 1 shows the free tRNA 3 Lys .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated different domains of the (12-53)NCp7 are unable to anneal tRNA 3 Lys to RNA-(77-257). Fixed concentrations of [ 33 P]tRNA 3 Lys and RNA-(77-257) (5.10 Ϫ12 mol of each denaturated RNA/ assay) were incubated in a buffer with 25 mM Tris-HCl (pH 7.5), 0.1 mM MgCl 2 , and 80 mM NaCl, for 30 min at 37°C, in the presence of 20, 80, and 150 molar equivalents of (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) NCp7 (lanes 2-4, respectively), (34 -51)NCp7 (lanes 5-7, respectively), and (13-56)NCp7dd (lanes 8 -10, respectively). Lane 1 shows the free tRNA 3 Lys .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have underlined the importance of Trp 37 in HIV-1 (19,26,27), its replacement by a nonaromatic amino acid leading to a loss of viral infectivity. When, Trp 37 was replaced by a hydrophobic amino acid such as leucine in Leu 37 (12-53)NCp7, no ternary complex was observed, illustrating the crucial importance of Trp for the NCp7 hybridase activity.…”
Section: Ncp7 Zinc Fingers Are Required For Trna Annealing 4821mentioning
confidence: 99%
“…The peptide VKCFNCGKEG-HIARNCRA and similar peptides have been extensively studied by numerous investigators as model zinc fingers (2,(11)(12)(13)(14)(15)(16)(17). This peptide has been shown to adopt zinc finger-like structure and bind double-stranded deoxyribonucleotides in solution (18).…”
Section: Binding Of Cobalt Complexes To a Model Zinc Finger Peptidementioning
confidence: 99%
“…For instance, binding of an intercalating drug induces a specific modification of the 260-nm band in the RNA transactivation response element RNA CD spectrum (28). Phosphorescence and optically detected magnetic resonance studies reported modifications of tRNA base stacking induced by NCp7 binding (29). Moreover, RNA unwinding should induce more significant changes in CD spectra.…”
Section: /Hismentioning
confidence: 99%